Analisis Kebutuhan Pengembangan E-booklet Bernuansa Emotional Spiritual Quotient pada Materi Sel - Humaira, Assyifa; Lufri (Al-Alam: Islamic Science Education Journal, 2026)
Teaching materials play a crucial role in increasing students' learning motivation, because the use of teaching materials that are appropriate to the characteristics of students and learning materials can create a more interesting and interactive learning environment. One example of teaching materials is an e-booklet written in simple language, equipped with images related to the material, so that it can increase students' interest in reading. The purpose of this study was to analyze the need for e-booklets with emotional spiritual quotient nuances as a tool in biology learning, especially on cell material for Phase F of SMA/MA. The research method used was descriptive with quantitative and qualitative approaches. Data collection techniques were carried out through interviews with biology teachers and distributing questionnaires to grade XI students of SMA Dar El Iman. The results of the interviews showed that teachers had never used e-booklets with Emotional Spiritual Quotient (ESQ) nuances in biology learning. The conclusion of this study is the need for e-booklets with Emotional Spiritual Quotient nuances in cell material.